Seagrass (Zostera marina) transplant experiment reveals core microbiota and resistance to environmental change. Issue 19 (24th August 2022) - Adamczyk, Emily M.; O'Connor, Mary I.; Parfrey, Laura Wegener
Abstract: Zostera marina (seagrass) is a coastal marine angiosperm that sustains a diverse and productive ecosystem. Seagrass‐associated microbiota support host health, yet the ecological processes that maintain biodiversity and stability of the seagrass leaf microbiota are poorly understood. We tested two hypotheses: (1) Microbes select seagrass leaves as habitat such that they consistently host distinct microbiota and/or core taxa in comparison to nearby substrates, and (2) seagrass leaf microbiota are stable once established and are resistant to change when transplanted to a novel environment. We reciprocally transplanted replicate seagrass shoots (natural and surface sterilized/dead tissue treatments) among four meadows with different environmental conditions and deployed artificial seagrass treatments in all four meadows. At the end of the 5‐day experiment, the established microbiota on natural seagrass partially turned over to resemble microbial communities in the novel meadow, and all experimental treatments hosted distinct surface microbiota. We consistently found that natural and sterilized/dead seagrass hosted more methanol‐utilizing bacteria compared to artificial seagrass and water, suggesting that seagrass core microbiota are shaped by taxa that metabolize seagrass exudates coupled with minor roles for host microbial defence and/or host‐directed recruitment. We found evidence that the local environment strongly influenced the seagrass leaf microbiota in natural meadows and that transplant location explained more variation than experimental treatment. Transplanting resulted in high turnover and variability of the seagrass leaf microbiota, suggesting that it is flexibly assembled in a wide array of environmental conditions which may contribute to resilience of seagrass in future climate change scenarios.